Analisis Pemecahan Masalah Materi Vector Dengan Metode Polya Dari Gaya Belajar - Yenni Novita Harahap; Ayu Rahmawati; Fitri Khairani Pulungan; Nabila Faiza Dalimunthe; Neni Herawati; Nurfadila Ulfa Siregar; Nurhabibi Fakhri (Journal on Education, 2023)
vector is one of the concepts that must be mastered by students of the mathematics education study program presented in vector analysis courses. One of the discussions in mathematics is vector material. vector is one of the mathematical materials which is considered quite difficult, and based on the results of observations and interviews it is known that students still have difficulty learning the abstract concept of vector analysis. students have difficulties in mastering the basic terms of vectors to the application of vectors with differentiation and integration. even though the concept of vector analysis is one of the provisions of knowledge and skills that must be mastered by prospective mathematics teacher students. One of the strategies to increase students' understanding of material is to provide problems as a stimulus. so that it is necessary to develop learning resources, one of which is in the form of a mathematics module. Mathematics education students at FKIP Univa Medan 2023 who have taken vector analysis courses. The instruments in this study consisted of two types, namely the main instrument and the auxiliary instrument. the main instrument is the researcher himself because the researcher will directly supervise the field conditions and as a direct digger of data. while there are two types of auxiliary instruments, namely test instruments and interview guides. The data in this study are data on written tests and data from interviews on dot multiplication and cross.